Optimal Groundwater Management in Teeb Area, Missan Province, Using Genetic Algorithm Technique - Al-Aboodi, Ali H.; Al-Tai, Majeed A.; Al-Kadhimi, Ahmed M. (Basrah Journal for Engineering Sciences, 2013)
A linked simulation-optimization model for obtaining the optimum management of groundwater flow is presented in this research. (MODFLOW, 98) packages are used to simulate the flow of the groundwater system. This model is integrated with an optimization model which is based on the genetic algorithm (GA). Three management cases were undertaken by running the model with adopted calibrated parameters. In the first case found the optimum value of the objective function is (0.32947E+08 m3/year), in other words, the pumping rates could be raised to nine times the current pumping rates, with a highest decline in the hydraulic heads of groundwater compared with initial hydraulic heads reached to 6 cm. In a second case twenty six wells out of thirty five can be operated with "on/off" status associated with each well to obtain the maximum value of pumping rate. In third case is allowed to move a location of well anywhere within a user defined region of the model grid until the optimal location is reached. The optimum value of objective function in third case is (0.35539E+08 m3/year) with 8% increasing of the pumping rates compared with the first case. This is due to the random distribution of existing well locations.